Coronary Slow Flow and Abnormal Nocturnal Blood Pressure Profile in Normotensives. (1st June 2013) - Durmaz, Tahir; Keles, Telat; Erdogan, Kemal Esref; Ayhan, Huseyin; Bilen, Emine; Akcay, Murat; Bayram, Nihal Akar; Bastug, Serdal; Bozkurt, Engin
Abstract : Background: Abnormal nocturnal blood pressure (BP) profile has been linked to microvascular function and autonomic dysfunction. However, no data were available regarding nocturnal BP profile in coronary slow flow (CSF). Aim: The aim was to investigate any association between CSF and abnormal BP response in normotensive patients. Methods: Consecutive 45 patients with CSF and 45 patients with normal blood flow during coronary angiography underwent 24-hour ambulatory BP monitoring. Hemodynamic parameters including 24-hour, daytime and nighttime systolic/diastolic/mean/pulse pressures, and BP % changes were obtained. Dippers, nondippers, and reverse dippers were determined. Results: Baseline characteristics of both groups were well matched except for TIMI (Thrombosis in Myocardial Infarction) frame counts for all major epicardial coronary arteries. No statistical significance was detected regarding to hemodynamic parameters obtained by 24-hour ambulatory BP monitoring. The prevalence of nondippers was higher in CSF patients compared with controls (51.1% vs 28.9%, respectively). In univariate analysis, systolic BP change (%), 24-hour diastolic BP, diastolic BP change (%), 24-hour mean BP, mean BP change (%), nondipper/reverse dipper, and separately nondipper status were found to be significant predictors for CSF. However, in multivariate logistic regression analysis, systolic BP change (%) (odds ratio [OR], 0.934; 95% confidence interval [CI], 0.874–0.998; P = 0.045), nondipper/reverse dipper status (OR, 0.505; 95% CI, 0.265–0.962; P = 0.038), and separately nondipper status (OR, 0.317; 95% CI, 0.126–0.797; P = 0.015) were found to be significant predictors for CSF. Conclusion: The frequency of nondippers was higher in slow flow, and there was a significant association between CSF and abnormal nocturnal BP profile in normotensives.